PENINGKATAN LITERASI DAN TATA KELOLA INFODEMIK COVID 19 BAGI KOORDINATOR TENAGA KEPENDIDIKAN UNIVERSITAS MULAWARMAN - Bakhtiar, R.; ,, Yuniati; Sawitri, E.; Miharja, E. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
Even though the number of Covid-19 cases has decreased and the vaccination participation rate is quite high, there is still misinformation about Covid-19. Various new variants and uncontrolled pandemics encourage the massive spread of information that tends to be misleading, known as the infodemic. At Mulawarman University, efforts to prevent the spread of Covid-19 are constrained by a low understanding of the pattern of the spread of the SARS-COV2 virus so education staff need education and are expected to act as agents of change in counteracting the Covid-19 infodemic in their respective faculties. The aim of this community service is to educate educational staff as managers of the Covid-19 infodemic on campus. This activity was attended by 20 faculty coordinators and rectorate staff. The training material was updated Covid-19, infodemic governance and media literacy carried out through blended learning and lecture methods. The final evaluation of the training showed the participants' knowledge and understanding of the infodemic and their resulting agreement to disseminate information to education staff, lecturers and students so that they can become leaders in reducing the Covid-19 infodemic among the academic community. Keywords: infodemic, management, coordinator - Covid-19